Enhancement of CO2 adsorption on activated carbon prepared from Canarium ovatum Engl. nut shells - Yao, Marina G. (Animo Repository, 2015)
New sources of activated carbon (AC) are desired for CO 2 capture. This study explored the potential of Philippine indigenous Pili tree (Canarium ovatum Engl.) waste nut shell as a source of new activated carbon. The charred sample has high fixed carbon content (86.81%), which upon activation, showed higher surface area (701 m 2 /g) and larger pore volume (0.45 cm 3 /g) compared to the unactivated sample. Modification of the carbon surface through impregnation of different amines resulted in lower surface areas, narrower pore volumes, and changes in morphology (from uniform geometric shape to spongy microstructures). The amine modified samples gave slight decrease in X-ray diffraction interlayer spacing (d (002) ) resulting in formation of micro crystallites that may promote CO 2 adsorption. Indeed, the modified AC samples had higher adsorption capacities for CO 2 than the original AC. The amount of adsorbed CO 2 on pentaethylenehexamine-modified AC was up to 2.380 mmol/g at 1 atm and 293 K, a 173% increase in comparison with that of the original AC. © 2015, Science and Technology Information Institute. All rights reserved.